Robot dynamics models in terms of generalized and quasi-coordinates: A comparison - Kozłowski, Krzysztof (1951-2021) (Zielona Góra: Uniwersytet Zielonogórski)
Lagrangian robot dynamics derived by making use of the generalized and quasi-coordinates is discussed. A comparison between two sets of equations is presented, which is motivated by recently developed (Jain and Rodriguez, 1994) diagonalized equations of motion for multibody open kinematic chains with N degrees of freedom. These equations are derived by making use of new joint velocity variables vi which can be viewed as time derivatives of the Lagrangian 'quasi-coordinates, similar to those in classical mechanics.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka